Cytotoxic T cells in chronic idiopathic neutropenia express restricted antigen receptors. Issue 12 (2nd December 2017) - Mastrodemou, Semeli; Stalika, Evangelia; Vardi, Anna; Gemenetzi, Katerina; Spanoudakis, Michalis; Karypidou, Maria; Mavroudi, Irene; Hadzidimitriou, Anastasia; Stavropoulos-Giokas, Catherine; Papadaki, Helen A.; Stamatopoulos, Kostas
Abstract: Chronic idiopathic neutropenia (CIN) is an acquired disorder of granulopoiesis characterized by female predominance and mostly uncomplicated course. Crucial to CIN pathophysiology is the presence of activated T lymphocytes with myelosuppressive properties in both peripheral blood (PB) and bone marrow (BM). We systematically profiled the T cell receptor beta chain (TRB) gene repertoire in CD8 + cells of 34 CIN patients through subcloning/Sanger sequencing analysis of TRBV–TRBD–TRBJ gene rearrangements. Remarkable repertoire skewing and oligoclonality were observed, along with shared clonotypes between different patients, alluding to antigen selection. Cross-comparison of our sequence dataset with public TRB sequence databases revealed that CIN may rarely share common immunogenetic features with other entities, however, the CIN TRB repertoire is largely disease-biased. Overall, these findings suggest that CIN may be driven by long-term exposure to a restricted set of specific CIN-associated antigens.